Eocene (46–44 Ma) Onset of Australia‐Pacific Plate Motion in the Southwest Pacific Inferred From Stratigraphy in New Caledonia and New Zealand. (7th July 2020) - Dallanave, Edoardo; Maurizot, Pierre; Agnini, Claudia; Sutherland, Rupert; Hollis, Christopher J.; Collot, Julien; Dickens, Gerald R.; Bachtadse, Valerian; Strogen, Dominic; Morgans, Hugh E. G.
Abstract: The Pacific plate circuit went through a complex reorganization during the early to middle Eocene, approximately coinciding with the onset of subduction along the western Pacific margin. However, the timing and dynamics of this change in the southwest Pacific and evolution of subduction beneath the Tonga‐Kermadec Arc are not fully resolved. We present magneto‐biostratigraphic data from an early to middle Eocene sedimentary section exposed in the Koumac‐Gomen area, New Caledonia, which is an emerged portion of the Norfolk Ridge. The 260 m‐thick succession contains a transition from pelagic micrite to terrigenous‐rich calciturbidite that is observed regionally in New Caledonia and which is interpreted to represent a shift from sedimentation on a stable submarine plateau to slope formation developed under a convergent tectonic regime. The stratigraphic contact between pelagic micrite and overlying calciturbidite is not exposed, but our magnetic polarity‐based chronology constrains the age of transition to 46–44 Ma, in agreement with the 45.3 Ma age recently obtained from the Noumea area in southern New Caledonia. We integrate records from New Caledonia with recent magnetostratigraphic data from South Island, New Zealand, where marked variations in terrigenous input occurred during the early and middle Eocene. Synchronous sedimentary changes in the southwest Pacific occurred at the same time as onset of rapid seafloor spreading south of Australia and New Zealand. We infer that the underlying cause of stratigraphic change was inception of slip at a new configuration of the Australia‐Pacific plate boundary, which evolved into the Tonga‐Kermadec subduction system. Plain language summary: New Caledonia and New Zealand expose sedimentary rocks that hold the key for understanding regional tectonic evolution. Using rock magnetism and micropaleontology, we determine the age of sedimentary records in New Caledonia. A change in sedimentation style indicates the onset of tectonic activity about 45 million years ago, which is the same time that significant changes in depositional style and rate are recorded by sediments in New Zealand, and changes in spreading rate are recorded by magnetic anomalies south of Australia and New Zealand. We interpret our evidence as recording inception of a new plate boundary in the southwest Pacific that ultimately resulted in development of the southwestern portion of the Pacific Ring of Fire. Key Points: We present a new integrated magneto‐biostratigraphic age model for Eocene sedimentary rocks in New Caledonia The regional onset of sediment gravity flows at 46–44 Ma corresponds to the inception of rapid Australia‐Pacific plate motion Northern Zealandia sedimentary change during the middle Eocene was likely related to initiation of the Tonga‐Kermadec subduction